PHYTOCHEMICAL MANAGEMENT OF DIABETIC COMPLICATIONS, EXPERIMENTAL EVIDENCES - REKHA BISHT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
It is progressively obvious that not only is a cure for the current worldwide diabetes epidemic required but also for its major complications, affecting both small and large blood vessels. These complications occur in the majority of individuals with both Type-1 and Type-2 diabetes. Incidence and pervasiveness of diabetes mellitus are rapid becoming high in middle- and low-income countries where about 80% of people living in those countries depend on traditional medicines. Innumerable and diverse reports abound in the literature on studies conducted to investigate the ameliorative effects of medicinal plants on various pathophysiological complications of diabetes mellitus. Traditional medicines derived from medicinal plants are used by about 60% of the world’s population. Although there are various perspectives to reduce the ill effects of diabetes and its secondary complications, herbal formulations are preferred due to lesser side effects and low cost. The present review emphasizes on medicinal plants that could be beneficial for the treatment of diabetes-induced macrovascular and microvascular complications.